Treating families and children in the child protective system : strategies for systemic advocacy and family healing - Crenshaw, Wes (Family therapy and counseling series., 2004)
Crenshaw proposes a new integration of many of the existing theories and practices of family and child counselling with those of the welfare, child protection, and social services programs.